Earth's Last Frontiers | Jungle Worlds - Catherine Chambers (Oxford, United Kingdom Capstone Global Library Ltd, 2014)
Read this book to learn about one of Earth's last frontiers: mysterious jungles. Learn about the extreme weather, hidden landforms, and unusual living things found in this habitat.
Keywords: Life Sciences; Biomes and Habitat